The temperature of internet: Internet use and depression of the elderly in China - Guo, Hongwang; Feng, Shuyi; Liu, Ziming (Frontiers in Public Health, 2022)
This paper uses data from the China Health and Retirement Longitudinal Study in 2018 to investigate the impact of internet use on depression of the elderly. We employ the propensity score matching and endogenous switch regression model to address potential endogeneity. The results show that the elderly who are relatively young, male, well educated, live in urban area or small family are more likely to use the internet. The elderly who have healthy eyes, no agricultural employment, or those who are retired, not qualified to receive subsistence allowance or drink wines have a higher probability to use the internet. We also find that internet use significantly reduces the elderly’s depression status by 3.370 points, which is roughly equivalent to a reduction of 37.19%. Heterogeneity analysis reveals that the health effect is particularly large for agricultural workers, female or older elderly. Our results highlight the significant welfare effects of internet infrastructure development in China.